(3cJGH GdYGde hGdeJYdes - (3CHh MfjaI , CHh MfjaI,J (B150 (3g` s
(3ChdgG (B:s
(3Chdg MOKfG GdTjN CHh GdeYjf ejehf Hf eMeO Hf eMeO GdfSai Yf CHj MfjaI QVi Gddg Yfg Cfg bGd (B: (3GdMeO ddg MjkG dGjehJ, hUeOkG dGjWYe s
(3BNQgG (B:s
(3bGd YR hLd (B: (3jYQahf fYeg Gddg Ke HfcQhfgG Cf Jchf ef Gdgd GdhGMO GdPi djS ceKdg TF hgh Ydi cd TF bOjQ , hGdMeO ddg QH GdYGdejf Je cJGH GdYGde hGdeJYde s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJs
(3hYdi hQbI GdYfhGf efgG JedcGJ eMOKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs